EFFECT OF NPK LEVELS AND BIO-ORGANICS ON YIELD AND NUTRIENT REMOVAL BY BASMATI RICE CV. HUBR 10-9 . HUBR 10-9 - NANDA, GANGADHAR; MEENA, R. K.; S. P. SINGH, UPPU SAI SRAVAN (The Bioscan, 2016)
organics on basmati rice cv. HUBR 10-9. Results revealed that increasing NPK levels up to 100% RDF (120-60- 60 kg ha-1) significantly improved yield attributes, grain yield (52.28 q ha-1) and straw yield(78.19 q ha-1) as well as NPK removal by grain (75.52, 19.12 & 17.33 kg ha-1) and straw (53.31, 7.58 & 118.67kg ha-1). Combined application of FYM + BGA + PSB proved significantly superior resulted increase in grain yield (4.70 & 10.62%) and straw yield (5.02 & 10.96%) over FYM + BGA and FYM alone. Variety HUBR 10-9 shown higher grain and straw yield potential due to NPK application @100% RDF (120-60-60 kg ha-1) combined with FYM + BGA + PSB. Hence, study suggests no saving of fertilizer NPK possible even after integration of bio-organics to the earlier recommended NPK dose.